The Norton Anthology of Short Fiction - Cassil R.V. (New York W. W. Norton and Company, 1995)
Following the success of its predecessors, the Fifth Edition again offers a teachable balance of contemporary and classic short fiction, including new stories by Margaret Atwood, Toni cade Bambara, Donald Barthelme, Raymond Carver, Julio Cortazar, Timothy Findley, Richard Ford, Charlotte Perkins Gilman, Nadine Gordimer, Barry Hannah, Zora Heale Hurston, Jamaica Kincaid, Bharati Mukherjee, Amy Tan, Guy Vanderhaeghe, and Eudora Welty, among others.
Keywords: Literature